The Relationship among Student’s Domain of Learning Development Implementing Virtual Learning in Higher Learning Institutions - Nik Zulkarnaen Khidzir; Khairul Azhar Mat Daud; Mohd Asrul Hery Ibrahim (2016)
Virtual learning environments (VLEs) are the basic components of contemporary distance learning, but can also be integrated with a physical learning environment which may be referred to as blended learning. The success of a VLEs implementation depends to a considerable extent on student acceptance and use of such an e-learning system. Therefore, the aim of this study is to determine the relationship among domains of learning (cognitive, psychomotor and affective) of the student’s in the implementation of VLEs in Higher Learning institutions. Through the purposive sampling techniques, questionnaires were distributed to 113 academic scholars in higher learning institutions (HLI) from various academic qualification, expertise and experiences. All hypothesis tested were significant. However, results of the correlation coefficient (r) values < 0.4 verifies that a weak positive relationship exists among all the domains of learning. Findings reveal that all the cognitive, psychomotor and affective skill influence each other. Through the findings, HLI practitioners and technologist could consider the ease use for VLEs in order to encourage the cognitive, psychomotor and affective skill development.